Optimizing cryopreservation conditions for use of fucosylated human mesenchymal stromal cells in anti-inflammatory/immunomodulatory therapeutics - Gil-Chinchilla, Jesús I.; Bueno, Carlos; Martínez, Carlos M.; Ferrández-Múrtula, Ana; García-Hernández, Ana M.; Blanquer, Miguel; Molina-Molina, Mar; Zapata, Agustín G.; Sackstein, Robert; Moraleda, Jose M.; García-Bernal, David (Frontiers in Immunology, 2024)
Mesenchymal stem/stromal cells (MSCs) are being increasingly used in cell-based therapies due to their broad anti-inflammatory and immunomodulatory properties. Intravascularlyadministered MSCs do not efficiently migrate to sites of inflammation/immunopathology, but this shortfall has been overcome by cell surface enzymatic fucosylation to engender expression of the potent E-selectin ligand HCELL. In applications of cell-based therapies, cryopreservation enables stability in both storage and transport of the produced cells from the manufacturing facility to the point of care. However, it has been reported that cryopreservation and thawing dampens their immunomodulatory/anti-inflammatory activity even after a reactivation/reconditioning step. To address this issue, we employed a variety of methods to cryopreserve and thaw fucosylated human MSCs derived from either bone marrow or adipose tissue sources. We then evaluated their immunosuppressive properties, cell viability, morphology, proliferation kinetics, immunophenotype, senescence, and osteogenic and adipogenic differentiation. Our studies provide new insights into the immunobiology of cryopreserved and thawed MSCs and offer a readily applicable approach to optimize the use of fucosylated human allogeneic MSCs as immunomodulatory/anti-inflammatory therapeutics.